(3GdEfUGa aj eSGFd GdNdGa (B((3Hjf GdHUQjjf hGdchajjf(B)s - (3YHO GdQMef Hf eMeO Hf YHjO Gddg GdCfUGQj , GHf GdCfHGQj, ceGd GdOjf CHh GdHQcGJ,J (B577 (3g` s ((3eMeO Hf bGSe Hf eMeO Hf SYO GdUYOj s)
(3ChdgG (B:s
(3PcQ Gdchajhf Edi Cf GdGSe eTJb ef GdhSe hgh GdYdGeI s
(3BNQgG (B:s
(3aUGQJ EVGaI GdYOO EdjgG HefRdI EVGaJg Edi GdLeY KhH hKdGK aj bhdge KdGKI CKhGH hYTQI heG CTHg Pdc hGddg CYde Je GdcJGH s
(3fSNI KGfjIs
(3JJab BNQgG eY BNQ GdfSNI GdChdi HGNJdGa jSjQ LOkG aj GdCdaGXs
(3hHgG fXGe GdJYbjHI WeSJ SfI GdfSN YeOkGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B327 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B183 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B519s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B41 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B182s
Keywords: (3GdfMhs